2019
DOI: 10.1002/arco.5177
|View full text |Cite
|
Sign up to set email alerts
|

Residue and use‐wear analysis of non‐backed retouched artefacts from Deep Creek Shelter, Sydney Basin: Implications for the role of backed artefacts

Abstract: A previous use-wear and residue analysis of backed artefacts from Deep Creek Shelter showed that they had a range of functions and had been used with a variety of raw materials. Were non-backed retouched flakes at Deep Creek used for different purposes? To answer this question, 40 non-backed specimens were selected for microscopic use-wear and residue analysis. Not all of these non-backed artefacts had been used, but we identified that many were scrapers, knives, incisors and saws. These tools were used for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…At least in southeastern Australia these functional claims have been thoroughly refuted. In sites with good organic preservation, residue and wear evidence of hafting has been documented, and the rates of hafting are identical for both microliths and other retouched flakes (Robertson et al 2019); hence hafting in itself is not evidence that microliths were part of projectiles. More importantly the residue and wear evidence is not compatible with claims for microliths predominantly being projectile armatures.…”
Section: Small Changes In Australiamentioning
confidence: 99%
See 3 more Smart Citations
“…At least in southeastern Australia these functional claims have been thoroughly refuted. In sites with good organic preservation, residue and wear evidence of hafting has been documented, and the rates of hafting are identical for both microliths and other retouched flakes (Robertson et al 2019); hence hafting in itself is not evidence that microliths were part of projectiles. More importantly the residue and wear evidence is not compatible with claims for microliths predominantly being projectile armatures.…”
Section: Small Changes In Australiamentioning
confidence: 99%
“…More importantly the residue and wear evidence is not compatible with claims for microliths predominantly being projectile armatures. A series of high quality use-wear and residue studies have now demonstrated that microliths were used for varied craft tasks involving multi-purpose cutting and slicing and gouging of both plants and animal materials (Attenbrow et al 2009; Robertson et al 2009; 2019). These studies show no evidence for the use of microliths as projectile armatures, instead they document a large diversity of uses on similar shaped microliths: bone graving, hide scraping, plant scraping and cutting, meat cutting, wood carving, feather whittling, and others.…”
Section: Small Changes In Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…Continent-wide studies of backed artefacts show regional distinctions in shape, no matter what their material, indicating that raw material is not creating those large-scale differences (Hiscock & Maloney, 2016). Similarly, function has limited explanatory power with regards to backed Archaeology in Oceania 215 artefacts, as both wear features and residues give evidence that backed artefacts were used as craft tools that worked multiple materials in multiple ways (Attenbrow et al, 2009;Boot, 1993;Robertson et al, 2009Robertson et al, , 2019Robertson & Attenbrow, 2008). In addition, non-backed artefacts, formerly called "scrapers", have also been shown to have been used for a similar range of functions as backed artefacts from the same sites (Robertson et al, 2019), soundly decoupling function from backing retouch.…”
Section: Introductionmentioning
confidence: 99%